RELATIONSHIP BETWEEN BREAST CANCER LITERACY AND AWARENESS ABOUT BREAST SELF-EXAMINATION AMONG FEMALE STUDENTS IN PUNJAB, PAKISTAN - Qaisar Khalid Mahmood; Muhammad Uzair; Omair Azam (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Pakistan has the highest incidence rate of breast cancer in Asia. Pakistani women are at an increased risk of developing breast cancer. This risk necessitates breast cancer health education and literacy for women. Women who are educated about the disease and have positive healthcare seeking behaviors can timely diagnose this disease. This can significantly reduce the mortality rate of breast cancer and the national burden of this disease. This study aims to conduct an empirical study to assess breast cancer literacy and attitude towards breast self-examination (BSE) among females studying at university level in Pakistan. For this purpose, a cross sectional survey was conducted in different universities of Multan, Lahore and Rawalpindi and 857 female students successfully completed the survey. Breast cancer literacy was measured through two constructs; knowledge about the symptoms of breast cancer and awareness about the risk factors of breast cancer. The respondents were also asked about the knowledge of BSE and the procedure of performing of BSE. This study concluded that female university students had higher level of knowledge about the symptoms of breast cancer. The findings indicate that almost two-thirds of respondents replied that they had never performed BSE. More than half of the respondents also wanted to learn about BSE. The results indicate that there was a significant relationship (x2 =5.633, p<.05) between knowledge about the symptoms of breast cancer and performing BSE at your own. Thus, there is a need to arrange workshops or seminars for female university students to train them on BSE.